2020
DOI: 10.3390/ijms21238957
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Treatment with FTY720 Starting after Onset of Symptoms Reverses Synaptic Deficits in an AD Mouse Model

Abstract: Therapeutic approaches providing effective medication for Alzheimer’s disease (AD) patients after disease onset are urgently needed. Previous studies in AD mouse models suggested that physical exercise or changed lifestyle can delay AD-related synaptic and memory dysfunctions when treatment started in juvenile animals long before onset of disease symptoms, while a pharmacological treatment that can reverse synaptic and memory deficits in AD mice was thus far not identified. Repurposing food and drug administra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…Although high frequency stimulation induced conventional LTP at SC-CA1 synapses was reported previously to be impaired in 5–6-month-old animals of the same APP/PS1 mouse strain used in the present study [ 10 , 35 ], our above-described results showed that t-LTP tested was not significantly altered at this age. Since we argued that the proximity of Aβ plaques to the recorded CA1 neuron might be decisive to observe significant t-LTP deficits in APP/PS1 animals, we next focused on t-LTP in CA1 neurons in the vicinity of Aβ plaques that we visualized by staining with the dye methoxy-X04 (for staining procedure, compare Methods).…”
Section: Resultssupporting
confidence: 44%
See 4 more Smart Citations
“…Although high frequency stimulation induced conventional LTP at SC-CA1 synapses was reported previously to be impaired in 5–6-month-old animals of the same APP/PS1 mouse strain used in the present study [ 10 , 35 ], our above-described results showed that t-LTP tested was not significantly altered at this age. Since we argued that the proximity of Aβ plaques to the recorded CA1 neuron might be decisive to observe significant t-LTP deficits in APP/PS1 animals, we next focused on t-LTP in CA1 neurons in the vicinity of Aβ plaques that we visualized by staining with the dye methoxy-X04 (for staining procedure, compare Methods).…”
Section: Resultssupporting
confidence: 44%
“…Since we argued that the proximity of Aβ plaques to the recorded CA1 neuron might be decisive to observe significant t-LTP deficits in APP/PS1 animals, we next focused on t-LTP in CA1 neurons in the vicinity of Aβ plaques that we visualized by staining with the dye methoxy-X04 (for staining procedure, compare Methods). Stained Aβ plaques in APP/PS1 mice were visible in stratum radiatum, stratum oriens, and in the pyramidal cell layer of the CA1 area, but at this age (6-month), the density of Aβ plaques is relatively sparse (compare [ 10 , 36 ]). Thus, we decided to record t-LTP selectively in CA1 pyramidal neurons in the vicinity of Aβ plaques.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations